African Union's Economic, Social and Cultural Council : an evaluation of its mandate of facilitating civil society participation in the African Union - Grace Wakio Kakai (2006)
"The OAU was a state-centric system. It is only in the last years of its existence and in the transition from the OAU to the AU that discussions on modalities for facilitating civil society participation in its activiites commenced. The AU Act emphasises the need to build partnerships between governments and all sectors of civil society. Enhancing civil society participation is one of the AU's objectives and principles. To achieve this objective, the AU Act created the Economic, Social and Cultural Council (ECOSOCC) as an AU organ. ... Following this introductory chapter, the second chapter will analyse ECOSOCC's legal framework and structure in relation to its facilitation of civil society participation in the AU. ECOSOCC's legal framework's conceptualisation of civil society and the concerns it raises will be discussed. Linked to the conceptualisation of civil society is the role ECOSOCC will play within the AU institutional structure, therefore this will also be discussed. In addition, ECOSOCC's legal framework will be analysed to identify whether it is in line with associative or deliberative democarcy. An examination of how ECOSOCC can utilise its linkages with the other AU organs to channel civil society's views will also be carried out. The discussion of the ESC and UN ECOSOC and the lessons to be learnt from them will be done in the third chapter. The fourth chapter will set out the study's conclusions and recommendations." -- Introduction
http://www.chr.up.ac.za/academic_pro/llm1/dissertations.html
Prepared under the supervision of Mr. Mohamed Habib at the Faculty of Law, Addis Ababa University, Ethiopia
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.
314607 bytes
application/pdf
English
Keywords: African Union -- Economic, Social and Cultural Council (ECOSOCC); Economic, Social and Cultural Council of the African Union (ECOSOCC); African Union; Civil society; Democracy; Political participation; Text